Meningkatkan Keterampilan Berpikir Kritis Siswa Muatan Ipa Tema 7 Menggunakan Kombinasi Model Pbl, Savi, Make A Match Kelas Iv Sdn Belitung Utara 3 Banjarmasin - Febry Agustina; Amberansyah (CV. ITTC INDONESIA, 2023)
The problem addressed in this research is the low critical thinking skills of students, which affects their learning outcomes in the subject of Electricity in Science. The objective of this study is to describe the teacher's activities, analyze student activities, analyze critical thinking skills, and examine learning outcomes. This research adopts a qualitative approach with a classroom action research design conducted over four meetings. The research subjects consist of 20 students from the fourth grade of SDN Belitung Utara 3 Banjarmasin, comprising 10 male and 10 female students. Both qualitative and quantitative data are collected in this study. Qualitative data are obtained through observations of the teacher's activities, student activities, and students' critical thinking skills, while quantitative data are gathered from student learning outcomes. The findings of this research indicate that the teacher's activities in the fourth meeting meet the criteria of